HackProInit: AI Powered Hackathon Project Initiator - Santhanamari, G; N, Viswa Kumar; J, Sriniketh; M R, Abinaya; P, Aiswarya (2024 International Conference on Smart Systems for Electrical, Electronics, Communication and Computer Engineering (ICSSEECC), 2024)
HackProlnit is a dynamic platform designed to streamline the initial stages of hackathon project development. With a focus on generating project ideas, descriptions, and titles, it serves as a catalyst for participants seeking inspiration and direction. Leveraging state-of-the-art technologies such as Cohere for idea generation and OpenAI for project implementation, the platform offers a holistic approach to project initiation. The backend infrastructure, built on Node.js, facilitates seamless communication between the frontend and various APls, overcoming challenges such as CORS errors through innovative solutions. The frontend, developed using React.js and styled with Ant Design and Bootstrap, provides an intuitive user experience. A responsive landing page, meticulously crafted with Ant Design, showcases the project's functionalities and features, highlighting its value proposition. Key accomplishments include mastering NLP model interpretation for optimal query results, overcoming CORS challenges, and delivering a compelling user interface within tight time constraints. The platform's success lies in its ability to empower hackathon participants with the tools and guidance needed to kickstart their projects effectively.